Mechanisms of RNAi: a molecular view or Argonaute: the secret life of Slicer - Joshua-Tor, Leemor (Henry Stewart Talks, 2007)
Impact of RNAi on biology, Gene silencing, Mechanism of unravelling, Understanding the mechanism of RNAi related pathways, Transcriptional and post-transcriptional gene silencing, DNA elimination in tetrahymena, Mechanistic aspects of RNAi, The argonaute protein
Reviewed at 2020/09/10